Comfort fitting using thermoplastic polyurethane (TPU) - Zhang, Zhonghua (2018)
The comfort fitting mean that the items can be provided just right feeling for the consumer , it include wide range of the personal items, like as footwear, cloths, jewellery, mask, contact lens, etc. In the project, there was focus on the footwear, because footwear are very important for the consumer, footwear are central to consumers lifestyle and surprisingly to their everyday health. Poorly designed footwear can caused the short and long-term health problem. In fact, footwear can have a direct impacting in many parts our body. All the time, many people very hard to find the fitness shoes for themselves. The shape memory polymer materials may be provided good solution for the comfort fitting. Thermoplastic polyurethane is one of the shape memory polymer materials. In this project, two experiments will be discovered and demonstrated the possible comfort fitting solutions using shape memory polymer materials. According to the experimental results, it will give us an intuitive understanding of shape memory polymer material properties, included shape fixity, shape recovery, and elasticity. In this project, two sock-soles with different shape memory polymer material were designed and fabricated. One is child’s sole which fabricated via 3D printing using eflex filament. Another one is Adult’s sole which fabricated via 3D printing using TPU material. In the room temperature, the customized shape of shoes can be remained and fitted many times, after heating to slight above body temperature, the sock-soles becomes soft and elastic, we can pull the sock-shoes to fitness size, after cooling back to room temperature, the sock-soles becomes slight harder. Same ii heating process without external force one the sock-shoe, the sock-shoes’ shape can be reversed back to original shape. In this project, the design, fabrication and demonstration process were included.